A comparison of ketamine with pentazocine for analgesia in propofol based total intravenous anaesthesia for short surgical procedures - Okonkwo, Ugochukwu N.; Ewah, Richard L.; Ebirim, Longinus N. (International Journal of Research in Medical Sciences, 2022)
Background: Total intravenous anaesthesia is advantageous in that it avoids the use of volatile anaesthetic agents associated with a high cost of its delivery devices and operating theatre pollution. The ideal drugs for TIVA are not readily available in our environment, therefore suitable alternatives need to be studied. Objectives of current study was to compare the analgesic effects using a change of ≥20% in the patient haemodynamics and side effects of ketamine and pentazocine in propofol-based TIVA for patients who underwent surgical procedures less than 60 minutes. Methods: ASA 1 or 2 patients scheduled to have short surgical procedures were randomly allocated into two groups: PK and PP of 64 patients each. After the induction of anaesthesia, the patients received propofol infusion for maintenance of anaesthesia. Group PK, in addition, received a ketamine bolus of 0.5 mg/kg and group PP 0.7 mg/kg of pentazocine. Heart rate and blood pressure were monitored and recorded intraoperatively. The occurrence of respiratory depression, emergence reactions, PONV, were also recorded. Results: The differences in the incidence of a ≥20% rise in both the heart rate and the systolic blood pressure were not statistically significant in the two groups (p>0.05). For the diastolic blood pressure (DBP), no significant change was observed in group PK (p>0.05). In group PP, there was a statistically significant increase from induction until the 15th minute (p=0.006, 0.01, 0.01, 0.009). Conclusions: This study showed that the sub hypnotic dose of ketamine had the same analgesic efficacy as pentazocine in propofol based TIVA. It, however, ensured better stability in haemodynamics.